Young swimmers’ kinematic and hydrodynamic detraining between a two seasons’ break. - Costa, Mário (2016)
The aim of this study was to analyze the effects of the two seasons’ break period on young swimmers’ biomechanics taking into account their biological development. Twenty-five competitive swimmers were submitted to several anthropometric, kinematic and hydrodynamic tests at the end of the competitive season and 10 weeks later at beginning of the 2012-2013 season. The results showed that: (i) young swimmers can still improve their swimming biomechanics despite the absence of swim training between a two seasons’ break; (ii) those improvements can be explained by their biological development (i.e. anthropometrics).